Shame and eating psychopathology: exploring the role of self-judgment and fears of receiving compassion - Oliveira, Vanessa Raquel São Pedro de (2016)
Shame has been for long associated with the development and maintenance of body image and eating difficulties. However, the mechanisms underlying this association remain unclear. Therefore, the current study sought to examine the role of external shame on the endorsement in disordered eating attitudes and behaviours through the mechanisms of self-judgment and fears of receiving compassion from others, while controlling for body mass index (BMI). Participated in this study 400 women from general population, with ages ranging from 18 to 55 years old. Correlation results showed a significant and positive relationship between external shame, self-judgment, fears of receiving compassion from others and eating psychopathology. Path analyses results demonstrated that, when controlling for the effect of BMI, external shame had a direct impact on disordered eating severity, and an indirect effect mediated by higher levels of self-judgment and increased fears of receiving kindness and compassion from others. Results confirmed the plausibility of the tested model, which explained 36% of eating psychopathology’s variance. These findings seem to support that women who perceive that others view them negatively tend to endorsedefensive and maladaptive emotion regulation strategies (such as harsh critical attitudes towards the self and resistance at receiving compassion from others), which may trigger maladaptive eating attitudes and behaviours. The current research appears to be a pioneer study in the field of body image and eating-related psychopathology and seems to represent a new avenue for future research and for the development of intervention programs.